The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1007/s00429-019-01942-5
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the pituitary in psychopathologies: a review of in vivo magnetic resonance imaging studies

Abstract: The pituitary gland (PG) is a key component of the essential endocrine systems in humans and animals, including the hypothalamic-pituitary-adrenal, hypothalamic-pituitary-gonadal, and hypothalamic-pituitary-thyroid axes. Structural changes in the PG are observed in a number of psychiatric disorders. Psychiatric disorders are typically characterized by subtle, time-dependent anatomical changes in the brain, and their study necessitates highly powered, longitudinal investigations. Structural magnetic resonance i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 135 publications
(204 reference statements)
0
6
0
Order By: Relevance
“…Third, focusing on a community‐based adolescent sample may have limited the variance and severity of depressive/anxiety symptoms, which may explain why aPGV development was not found to mediate the association between ELS and psychopathology. Finally, despite the high inter‐rater reliabilities obtained in this study, intensity‐dependent delineation protocols have been criticized as being susceptible to the observer's biased perception of intensity and to intra‐individual variations of the pituitary “bright spot” (Anastassiadis et al., 2019). Replication in other cohorts is therefore required to further establish the validity of the proposed tracing protocol and the use of aPGV as an index to investigate the relationship between ELS and HPAA dysfunction.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Third, focusing on a community‐based adolescent sample may have limited the variance and severity of depressive/anxiety symptoms, which may explain why aPGV development was not found to mediate the association between ELS and psychopathology. Finally, despite the high inter‐rater reliabilities obtained in this study, intensity‐dependent delineation protocols have been criticized as being susceptible to the observer's biased perception of intensity and to intra‐individual variations of the pituitary “bright spot” (Anastassiadis et al., 2019). Replication in other cohorts is therefore required to further establish the validity of the proposed tracing protocol and the use of aPGV as an index to investigate the relationship between ELS and HPAA dysfunction.…”
Section: Discussionmentioning
confidence: 88%
“…Given that PGV has been postulated to reflect the number and/or size of ACTH‐secreting corticotrophs (Gertz et al., 1987; Westlund et al., 1985), PGV changes are likely to be largely determined by its anterior region. However, most PGV tracing protocols have failed to consider them as separate volumes, although it is well‐established that the anterior (but not posterior) PG is directly involved in the HPAA (Anastassiadis et al., 2019). The posterior lobe makes up less than 20% of the gland, leading some to argue that changes in PGV are likely to reflect variations in the volume of the anterior lobe (Krishnan et al., 1991; Pariante et al., 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The upregulated expression of genes was associated with chromatin modeling through chromatin, the accessibility mechanisms of serine threonine kinase 11 (Stk11) , Smarca4 , and AT-rich interactive domain ( Arid1a, BAF250a) , which impact the gene transcription process. Transcriptional factors, HIFs can bind to a specific binding site, hypoxia response element (HRE) in the promoter of the target gene ( 31 33 ), therefore, we propose that the HIFs are candidates for pioneer or non-pioneer factors that might be involved in the regulation of transcription during pituitary development and homeostasis during physiological and psychological stress ( 37 , 40 , 54 , 59 , 60 ). We demonstrated that hypoxic stress increased Crhr1 and Trhr and decreased Sstr2 ( Figures 3C , 5A ), while increasing Hif-1α in acute hypoxia ( Supplemental Figure 7A ) and decreasing Hif-2α in continuous hypoxia for 5 days.…”
Section: Discussionmentioning
confidence: 99%
“…The PG can easily be identified in the mid-sagittal plane, inferior to the hypothalamus ( Figure 1A ). It is bordered by the sphenoid sinus anteriorly and ventrally, the cavernous sinuses laterally, the dorsum sellae posteriorly, and the diaphragma sellae dorsally ( Anastassiadis et al, 2019 ). Pituitary segmentation was performed as in Jones et al (2023a) .…”
Section: Methodsmentioning
confidence: 99%